PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN IPAS KELAS IV SDN 41 AMPENAN - Savitri Rahmadin, Rizka; Husniati; Nurwahidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the influence of the Problem Based Learning model on students' critical thinking skills in learning science class IV SDN 41 Ampenan. The type of research used is quasi-experimental with the time series design. The population used in this study was all grade IV students of SDN 41 Ampenan totaling 32 people, who then became all members of the research sample so that they used a saturated sampling technique. The data collection instruments used in this study are in the form of description test sheets and observation sheets for the implementation of learning. Hypothesis testing uses a paired sample t-test with a significance level of 0.05. The results of the t-test obtained a significance value of 0.00, meaning that what was submitted was rejected and accepted. So that the results of this study can be concluded that the Problem Based Learning model affects students' critical thinking skills in learning science science class IV SDN 41 Ampenan.